Violence on the Chile-Peru border: Arica 1925-2015 - Freeman, Cordelia (2016)
This thesis examines the paradox of the Chile-Peru border, and specifically the Chilean border city of Arica, between 1925 and 2015. Through an eclectic mixed method ‘collage’, primarily relying on archival research and extended interviews, the richness of the lived experience of the border comes to the fore. Arica has been a space of violence since it was appropriated from Peru by Chile in the War of the Pacific (1879-1883) and I am interested in how this violence has lingered and manifested itself in various ways since Arica officially became Chilean territory in the 1920s. This violence often stems from a performance of Chilean machismo at the border. Arica is a space of contradiction. A space of extreme nationalism but also of rejection of the Chilean state, of being central to the Chilean nation but also of being peripheral and abandoned. Over five ‘border moments’ over ninety years Arica oscillates between centrality and marginality dependent on threats to Chilean sovereignty at the border. Through a chronological and multi-disciplinary arc the history of violence in Arica can be better understood. The thesis begins in 1925 when the United States became involved in the dispute over the Chile-Peru border that hadn’t been settled since the War of the Pacific. Violence permeated the region and made an attempted plebiscite impossible and although the border was demarcated through other means in 1929, Arica soon became ignored by the Chilean state. A state of abandonment remained until the 1950s when economic initiatives enacted at the regional level succeeded in raising the prospects and spirits of Arica, purging the area of violence, until the 1970s when General Pinochet’s new economic plan reversed Arica’s progress. Arica instead became a military space in this decade as tensions arose between Pinochet and Peruvian dictator General Velasco and international violence returned. This international level is then contrasted with violence at the corporeal level in Arica in the 1980s when HIV/AIDS and abortion both became increasingly pertinent at the border. The thesis closes with how violence remains present in Arica today, particularly as seen through the 2014 maritime border dispute.